In vitro antiproliferative effect of four ball-type phthalocyanines linked by t-butylcatechol and high singlet oxygen production - Canlica, Mevlude; Topcul, Mehmet Rifki; Cetin, Idil (TAYLOR & FRANCIS LTD, 2020)
Four ball-type phthalocyanines (H2Pc, MgPc, CoPc, and ZnPc) containing 4-tert-butylcatechol substituents at alpha-positions were synthesized from 3,3 '-(4-tert-butyl-1,2-phenylene)bis(oxy)diphthalonitrile. The structures were elucidated by elemental analysis and ultraviolet-visible, Fourier-transform infrared, proton nuclear magnetic resonance, and Maldi-Tof mass spectroscopies. The photophysicochemical properties of H2Pc, MgPc, and ZnPc were investigated in dimethylsulphoxide. The fluorescence quantum yields (phi(F)), triplet state quantum yields (phi(T)), and singlet oxygen quantum yields (phi(Delta)) with respect to H2Pc, MgPc and ZnPc were experimentally obtained. Furthermore, the degradation quantum yield (phi(d)) was evaluated for all complexes. Finally, the magnetic circular dichroism spectra of the four Pcs were obtained. Among these ball-type phthalocyanines, MgPc had the highest triplet lifetime and ZnPc had the highest singlet oxygen quantum yield. Moreover, the in vitro antiproliferative effect of ball-type phthalocyanines (H2Pc, MgPc, CoPc, and ZnPc) was evaluated on MCF-7 cell line originated from luminal A breast cancer and MDA-MB-231 cell line originated from triple negative breast cancer. For this purpose, cell viability MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay was used. For all compounds, 0.2, 0.4, 0.8, 1.6, 3.2, 6.4, 12.8, 25.6, 51.2, 102.4 mu M concentrations were applied to both cell lines. There was a significant decrease in cell viability for MCF-7 and MDA-MB-231 cells (p < 0.05).
Keywords: Ball-type phthalocyanines; high singlet oxygen quantum yield; MTT; antiproliferative effect; MCF-7; MDA-MB-23; MAGNETIC CIRCULAR-DICHROISM; NONLINEAR-OPTICAL RESPONSE; PHOTODYNAMIC THERAPY; METAL-FREE; 1,2-BIS(3,4-DICYANOPHENOXYMETHYL)BENZENE; METALLOPHTHALOCYANINES; PHOTOSENSITIZERS; TRANSFORMATION; FLUORESCENCE; BEHAVIOR; Chemistry